ANALYSIS OF THE RELATIONSHIP BETWEEN NURSING STUDENTS’ PERCEPTIONS OF THEIR PROFESSION AND THEIR ATTITUDES TOWARDS THEIR PROFESSION DURING THE COVID-19 PANDEMIC - Meşedüzü, Merve; Ayaz, Selin; BAYRAKTAR, SEMA; Onar, Melike; Bayraktar, Sema; Şeker, Simge; Tellioğlu, Hilal; Dursun , Şevval (My University, 2021)
ABSTRACT Introduction: It is known that nursing education, attitudes towards the profession are questioned and perceptions and attitudes of the nursing profession are evaluated. It may also have an impact on the Covid-19 pandemic. Purpose: It aimed to analysis of the relationship between nursing students- perceptions of their profession and their attitudes towards their profession during the Covid-19 pandemic. Method: The study, which was conducted as a descriptive, cross-sectional and relationship-seeking study, was applied to a total of 191 students in February 2021 through the survey form of BVU Nursing Department students. In the study, Sociodemographic Characteristics Data Form, Questionnaire Form for students- opinions about the nursing profession during the COVID-19 pandemic period and Attitude towards Nursing Profession Scale (HMYTÖ). These are HMÖ*, HMTED**, HMGD***. Statistical significance was calculated by using the p<0.05 value in the SPSS 22 program. Results: 58.1% are targeted to work in the field due to the Covid-19 pandemic process, and 41.9% are working in this field. Changing the mind at the point of designing the movement of Covid-19 is to change the dream of 11.5% of those who think and 88.5% of those who change the direction of thought. Here is one, it is significantly higher in terms of HMI (p=0.028) and HMGD (p=0.028) points compared to those who received it. Those who think that those who are in the Covid-19 pandemic process do not get the real value, HMGD average score is 042, compared to those who are thought to be entitled (p=0. HMYTÖ is significant compared to those who are self-sacrificing and self-sacrificing because of Covid 19 pandemics (p=0.042). Covid-19 pandemic Those who think that it does not have a negative effect on the nurse-s image, the HMGD is different on average compared to those who are considered in terms of score (p=0.031). Covid-19, regarding directing the gaze of the people who are directed according to the referrals, and the rotation of the changed people compared to the referrals, the HMGD scores are significantly higher than those who change the referral (p= 0.018) HMTED scores were small (p=0.018) Conclusion and suggestions: Although the students thought that nurses could not get the value they deserved even though they worked devotedly, it was revealed that their general attitudes towards their profession were positive. However, this situation has negatively affected their views on practicing the profession in the future and their outlook on the future. In addition, it has been revealed that nursing students- understanding of the importance of their profession in the Covid-19 period and realizing thesatisfying aspects of the profession affect their attitudes towards the profession positively, as well as they think that it also affects the image of the profession in a positive way. In this process, it was seen that the attitudes of the students working in any job were positive towards the profession. As a result, it is thought that for the positive development of nursing students- attitudes towards the profession, nurses should improve their working conditions and see the value they deserve in crisis situations. Keywords: Covid-19, attitude, nursing student, nursing profession
Keywords: Meşedüzü M., Bayraktar S., Tellioğlu H., Dursun Ş., Şeker S., Onar M., Ayaz S., -ANALYSIS OF THE RELATIONSHIP BETWEEN NURSING STUDENTS’ PERCEPTIONS OF THEIR PROFESSION AND THEIR ATTITUDES TOWARDS THEIR PROFESSION DURING THE COVID-19 PANDEMIC-, V. INTERNATIONAL CONFERENCE ON Covid-19 STUDIES, Ankara, Türkiye, 24 - 25 Eylül 2021, ss.236-238